Mapping Water Stress Incidence and Intensity, Optimal Plant Populations, and Cultivar Duration for African Groundnut Productivity Enhancement - Vadez, Vincent; Halilou, Oumarou; Hissene, Halime M.; Sibiry-Traore, Pierre; Sinclair, Thomas R.; Soltani, Afshin (Frontiers in Plant Science, 2017)
Groundnut production is limited in sub-saharan Africa (SSA) and water deficit or ‘drought’, is often considered as the main yield-limiting factor. However, no comprehensive study has assessed the extent and intensity of ‘drought’-related yield decreases, nor has it explored avenues to enhance productivity. Hence, crop simulation modelling with SSM (Simple Simulation Modeling) was used to address these issues. To palliate the lack of reliable weather data as input to the model, the validity of weather data generated by Marksim, a weather generator, was tested. Marksim provided good weather representation across a large gradient of rainfall, representative of the region, and although rainfall generated by Marksim was above observations, run-off from Marksim data was also higher, and consequently simulations using observed or Marksim weather agreed closely across this gradient of weather conditions (RMSE=99g.m-2; R2 = 0.81 for pod yield). More importantly, simulation of yield changes upon agronomic or genetic alterations in the model were equally predicted with Marksim weather. A 1º×1º grid of weather data was generated. ‘Drought’-related yield reduction were limited to latitudes above 12-13 degrees north in West Central Africa (WCA) and to the Eastern fringes of Tanzania and Mozambique in East South Africa (ESA). Simulation and experimental trials also showed that doubling the sowing density of Spanish cultivars from 20 to 40 plants m-2 would increase yield dramatically in both WCA and ESA. However, increasing density would require growers to invest in more seeds and likely additional labor. If these trade-offs cannot be alleviated, genetic improvement would then need to re-focus on a plant type that is adapted to the current low sowing density, like a runner rather than a bush plant type, which currently receives most of the genetic attention. Genetic improvement targeting ‘drought’ adaptation should also be restricted to areas where water is indeed an issue, i.e. above 12-13ºN latitude in WCA and the Eastern fringes of Tanzania and Mozambique.